Effect of cut height on indicators of forage production of Moringa oleifera cv. Plain - Padilla, C.; Fraga, Nidia; Scull, Idania; Tuero, R.; Sarduy, Lucía (Cuban Journal of Agricultural Science, 2016)
In a random block design with four replications, effect of cut height (10,20,and 30 cm) in the biomass production and yield components of Moringa oleifera cv. Plain in the indicators plant height, stem and leaf thickness, dry matter yield (DM) and population was studied during four consecutive cuts. The plant height showed irregular performance during the experiment, while the treatments did not affected the stem thickness (7.3-14.1mm) neither the leaf (0.2-0.5mm).The number of primary/ branches plant was higher (8) when was cut at 20-30cm, in the second and third cut .While the number of secondary branches was higher (P<0.001) when was cut at 20 and 30 cm high in the fourth cut. In the first cut, the DM yield was lower (P<0.05) when the plants were cut at 30cm high, without significantly differ among treatments in the remainder cuts. Plants population was no affected by treatments, but showed decrease in time. In the rainy period, the lowest content of phosphorous (P<0.01) was found when was harvested at 30cm high, while the ADF was lower (P< 0.01) when was harvested at 30 cm in the dry period. The remainder bromatological indicators studied were similar for all treatments, in both seasons of the year. The results indicated that the best cut height for this plant should be between 20-30 cm.Further studies are suggested where cut heights and cut frequency were combined to optimize the forage production. Key words: Moringa oleifera, cut height, indicators